Kelyphite Rims on Garnets of Contrast Parageneses in Mantle Xenoliths from the Udachnaya-East Kimberlite Pipe (Yakutia) - Lyudmila Pokhilenko (Minerals, 2021)
A new classification of kelyphitic rims on garnets from xenoliths of peridotitic and eclogitic parageneses of the mantle section under the Udachnaya-East kimberlite pipe (Yakutia) is presented. Five types of rims are identified: Rim1 develops between garnet and olivine/pyroxene (or rim2) and is composed of high-alumina pyroxenes, spinel, phlogopite; rim2, the coarse grain part of rim1, is located between rim1 and olivine/pyroxene, and mainly consists of phlogopite and less aluminous larger pyroxenes and spinel; rim3 develops between garnet and kimberlite, and presents with phlogopite and Fe-Ti spinel; rim4 sometimes presents instead of rim1/rim2 and consists of zoned high-Cr phlogopite with rare fine grains of chromium spinel; rim5, a “pocket” between garnet and rim1, is represented by microcrystalline aggregates of clinopyroxene, mica, spinel, calcite, and feldspar in different variations. Rims 1, 2, and 3 are typical for garnets of all studied parageneses. Rims 4 and 5 develop on high-Cr subcalcic garnets of the most depleted peridotites. Reactions of the formation of all types of rims are given in the article. Each type of kelyphite demonstrates a clear enrichment with a certain component: Rim1—MgO and alkalis; rim2—TiO 2; rim3—FeO and TiO 2 rim4—Cr 2 O 3 and rim5—CaO, suggesting the multistage injection of different components by mantle fluid.